1990
DOI: 10.1128/iai.58.2.536-542.1990
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages are stimulated by muramyl dipeptide to induce polymorphonuclear leukocyte accumulation in the peritoneal cavities of guinea pigs

Abstract: N-Acetylmuramyl-L-alanyl-D-isoglutamine (muramyl dipeptide [MDP]) injected intraperitoneally significantly increased the number of cells entering the peritoneal cavity of guinea pigs primed with liquid paraffin or thioglycollate. There was a close relationship between peritoneal polymorphonuclear leukocyte (PMN) accumulation and the uptake of glucosamine by macrophages in guinea pigs treated with a variety of bacterial cell surface components such as cell wall peptidoglycan subunits and bacterial or synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Apart from exerting antibacterial activity following infusion of alkaloids which decimated the intensity of sub-clinical mastitis, it mediated enhancement of somatic cell infiltration in the milk suggesting chemoattractant property of the alkaloids. These findings are consistent with previous studies in cows treated with some biological response modulator (De and Mukherjee 2013), or with cell wall product of Mycobacterium phlei in bovine SCM (Mukherjee et al 2004) and in guinea pigs treated with peptidoglycan subunit by intraperitoneal route (Nagao et al 1990).…”
Section: Discussionsupporting
confidence: 93%
“…Apart from exerting antibacterial activity following infusion of alkaloids which decimated the intensity of sub-clinical mastitis, it mediated enhancement of somatic cell infiltration in the milk suggesting chemoattractant property of the alkaloids. These findings are consistent with previous studies in cows treated with some biological response modulator (De and Mukherjee 2013), or with cell wall product of Mycobacterium phlei in bovine SCM (Mukherjee et al 2004) and in guinea pigs treated with peptidoglycan subunit by intraperitoneal route (Nagao et al 1990).…”
Section: Discussionsupporting
confidence: 93%
“…We have previously shown that guinea pigs exposed to aerosols of MDP microparticles (MPs) lead to morphological changes in AMΦ like pseudopodia formation and spreading (15). Nagao et al had targeted MDP to peritoneal macrophages (MΦs) in guinea pigs and showed that it induced activation (16). AMΦ are the first line of defense to inhaled foreign antigens.…”
Section: Introductionmentioning
confidence: 99%
“…BPLP‐PLA nanoparticles were fabricated by a single emulsion method . In order to increase THP‐1 cell targeting efficiency, we further modified drug‐laden nanoparticles with MTP, which has macrophage immuno‐potentiating effects without significant cytotoxicity . MTP was successfully conjugated with BPLP‐PLA and BPLP‐PLA‐PLX4032 nanoparticles by carbodiimide chemistry, as confirmed by Fourier transform infrared spectroscopy (FTIR) (Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 94%